(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Pure CdO thin films have been prepared on glass substrates by chemical bath deposition technique , films has Fe doping at ratio (0, 2,4,6,8)% to study effect of Fe doping on structural ,electrical properties of prepared films, structural properties has studies by (XRD),(AFM), electrical properties has such a direct electrical conductivity and Hall effect. XRD results showed that all prepared films has polycrystalline structural cubic type and higher crystal at plane (111) with decrease in grain size with doping increase. AFM results showed that the films has good smooth and homogeneous surface and decrease average roughness with doping increase, electrical results showed that electrical conductivity increasing with doping decreasing with two values of activation energy, Hall effect measurements showed that all prepared films has electrical conductivity n-type and increasing in carrier concentration number with doping increasing.